2017
DOI: 10.3390/rel8090168
|View full text |Cite
|
Sign up to set email alerts
|

Namaste Theory: A Quantitative Grounded Theory on Religion and Spirituality in Mental Health Treatment

Abstract: A growing body of research is beginning to identify characteristics that influence or are related to helping professionals' integration of clients' religion and spirituality (RS) in mental health treatment. This article presents Namaste Theory, a new theory for understanding the role of mental health practitioners' RS in clinical practice. Using Glaser's (2008) formal quantitative grounded theory approach, this article describes an emerging theme in the author's line of work-particularly that practitioners' in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…Chan (2010) found that having religious beliefs related to providing more spiritual care, although adherence to specific religions was not identified. These results align with findings that physicians and mental health practitioners with higher self-perceived spirituality and more frequent religious activity were more likely to discuss spiritual issues with patients and integrate spirituality into care (Oxhandler, 2017; Voltmer, Büssing, Koenig, & Zaben, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Chan (2010) found that having religious beliefs related to providing more spiritual care, although adherence to specific religions was not identified. These results align with findings that physicians and mental health practitioners with higher self-perceived spirituality and more frequent religious activity were more likely to discuss spiritual issues with patients and integrate spirituality into care (Oxhandler, 2017; Voltmer, Büssing, Koenig, & Zaben, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Given that helping professionals' intrinsic religiosity is a primary predictor of integrating clients' RS in practice (Oxhandler 2017), it is critical their RS beliefs and practices be assessed and considered, particularly when it comes to training practitioners to be mindful of their own RS beliefs and practices-and how they may differ from other professions and the clients they serve-as they ethically and effectively integrate clients' RS. Further, several interesting findings emerged from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In response to an emerging pattern between the practitioners' RS (particularly their intrinsic religiosity) and their integration of clients' RS, Namaste Theory was recently developed (Oxhandler 2017). Namaste is a Hindi term that means, "the sacred in me honors the sacred in you" (p. 1).…”
Section: Religion/spirituality In Health and Mental Health Treatmentmentioning
confidence: 99%
“…It is noteworthy that practitioners across these professions reported the importance of being aware of one's own RS beliefs (Crook‐Lyon et al., ; Delaney, Miller, & Bisonó, ; McNeil, Pavkov, Hecker, & Killmer, ; Oxhandler & Giardina, ). Self‐reflection and awareness of one's own RS is especially critical in these helping professions because intrinsic religiosity has been identified as a predictor of whether and the degree to which clients’ RS is considered in treatment (Kvarordt & Sheridan, ; Larsen, ; Oxhandler ; Oxhandler et al., ). Though the practitioners’ RS beliefs may assist in having empathy for the role RS has in clients’ lives, without proper training to maintain professional boundaries in this sensitive area of practice there is a risk of proselytization or inaccurately assuming an understanding of what a clients’ particular RS beliefs mean to him/her.…”
Section: Integration Of Rs In Clinical Practicementioning
confidence: 99%